2021
DOI: 10.1590/0034-7167-2020-0910
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Care model: Transition from acute to chronic care

Abstract: Objective: Description and discussion dimensions of Integrated Care Model. Methods: A descriptive study is done that describe a technological innovation, intervention strategies for professional performance. Results: Integrated Care Model (ICM) has two main categories include individual and Group-and disease-specific Model. First, is used for risky patients or with comorbidities. In second category; Chronic Care Model (CCM) is common form of Integrated Care Model to improve resultants in the patients with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(4 reference statements)
0
1
0
1
Order By: Relevance
“…The CIE model is guided by the evidence-based Chronic Care Model (CCM) and the multidisciplinary integrated care model through a restorative or enabling approach specified for the community-based eldercare system in China [ 18 , 19 ]. Minkman et al theorized how to implement integrated care and identified two most fundamental principles: engaging and empowering people and communities, population-oriented, and focusing on promoting health [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The CIE model is guided by the evidence-based Chronic Care Model (CCM) and the multidisciplinary integrated care model through a restorative or enabling approach specified for the community-based eldercare system in China [ 18 , 19 ]. Minkman et al theorized how to implement integrated care and identified two most fundamental principles: engaging and empowering people and communities, population-oriented, and focusing on promoting health [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nesse sentido, as evidências mais recentes de experiências bem-sucedidas de gestão do cuidado às pessoas com DCNT estão direcionadas para mudança deste modelo reativo, centrado na queixa/doença, para um modelo proativo, multidisciplinar, centrado na pessoa e no seu contexto sociocultural. Tratase do Modelo de Cuidados Crônicos (MCC), que propõe uma nova gestão da condição de saúde com intuito de obter resultados clínicos mais satisfatórios, monitoramento contínuo, desenvolvimento da corresponsabilização da pessoa sobre sua saúde e envolvimento da comunidade (5,6) .…”
Section: Introductionunclassified